Excellent performance of carbon-coated TiO2/Li4Ti5O12 composites with low Li/Ti ratio for Li-ion storage. Issue 113 (30th October 2015) - Yang, Wei; Bai, Xue; Li, Tao; Ma, Yuan-Yuan; Qi, Yong-Xin; Yin, Long-Wei; Li, Hui; Lun, Ning; Bai, Yu-Jun
Abstract : Carbon-coated TiO2 /Li4 Ti5 O12 composites with Li : Ti = 4 : 8 display high rate capacities and excellent long-term cycling performance at high current density. Abstract : TiO2 /Li4 Ti5 O12 composites with different Li : Ti molar ratios were fabricated by simply hydrolyzing tetrabutyl titanate in a water solution of LiNO3 and calcining the dried mixture at 600 °C, and the carbon-coated composites were prepared at 600 °C employing glucose as a carbon precursor. Compared to the carbon-coated TiO2 and Li4 Ti5 O12 prepared under the similar conditions, the carbon-coated TiO2 /Li4 Ti5 O12 composite with Li : Ti = 4 : 8 exhibits a stable capacity of 227.2 mA h g −1 when cycled 100 times at a current density of 100 mA g −1, and when cycled at 200, 400, 800 and 1600 mA g −1, the corresponding capacities are 206.1, 183.0, 152.4 and 119.4 mA h g −1 with the coulombic efficiency close to 100%. The composite also reveals outstanding long-term cycling stability at 500 mA g −1 with a reversible capacity of 177.6 mA h g −1 after 850 cycles. The enhanced electrochemical performance is ascribed to the synergistic effect of the two phases of TiO2 and Li4 Ti5 O12 with the carbon coating.